2023
DOI: 10.1371/journal.pone.0284102
|View full text |Cite
|
Sign up to set email alerts
|

Variation in salivary cortisol responses in yearling Thoroughbred racehorses during their first year of training

Abstract: Thoroughbred horses are bred for competitive racing and undergo intense training regimes. The maintenance of physical soundness and desirable behavioural characteristics are critical to the longevity of a racing career. Horses intended for Flat racing generally enter training as yearlings and undergo introductory training prior to exercise conditioning for racing. This period requires rapid adjustment to a novel environment. As a prey animal, a horse’s ‘fight-or-flight’ response is highly adapted, in which a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Acute stress can lead to an increase in various blood biomarkers, which act as protectors against changes in homeostasis during exercise [7]. However, good physical conditioning can reduce the stress load and promote adaptive metabolic processes associated with exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute stress can lead to an increase in various blood biomarkers, which act as protectors against changes in homeostasis during exercise [7]. However, good physical conditioning can reduce the stress load and promote adaptive metabolic processes associated with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, good physical conditioning can reduce the stress load and promote adaptive metabolic processes associated with exercise. This can also be reflected in the absence of variation in these biomarkers [7,18,39,40]. Studies have shown that cortisol, IL-6, and IL-1β remain stable during training, leading to improved performance in different equestrian sports, including classical and fieldwork on farms [4,12,20,39,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While many candidate mammal species may serve as models to understand the relative influence of physiological and social factors on cortisol production, horses ( Equus ferus caballus ) present a superior model for research given our deep understanding of both equine biology and sociality. There is a growing body of work originating from domestically kept horses on equine HPA responses to various physiological and social stressors using HCC, including husbandry [ 38 , 39 , 40 , 41 ], injury and illness [ 40 , 42 , 43 ], strenuous exercise [ 41 , 44 ], novel experiences [ 45 ], and seasonality [ 26 , 38 ]. The reproductive state of domestically kept female horses has shown both negligible correlation to cortisol levels [ 46 ] and also peak releases of cortisol in late pregnancy [ 47 ] and prepartum [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%